The Effect of Return on Assets, Debt to Equity Ratio, and Current Ratio on Stock Prices of Banking Sub-Sector (KBMI 3 and KBMI 4) Listed on the Indonesia Stock Exchange for the 2020–2024 Period - Muhammad Neza Qatrunada; Wiwin Aminah (JURNAL ECONOMINA, 2026)
This study aims to analyze the effect of Return on Assets (ROA), Debt to Equity Ratio (DER), and Current Ratio (CR) on stock prices of KBMI 3 and KBMI 4 banking sub-sector companies listed on the Indonesia Stock Exchange during the 2020–2024 period. This research is motivated by fluctuations in banking sector stock prices following the COVID-19 pandemic, which were not always aligned with changes in the companies’ fundamental financial ratios. In addition, inconsistencies in previous research findings regarding the influence of ROA, DER, and CR on stock prices have created a research gap that requires further investigation. The banking sector was selected because it plays a strategic role in the national financial system and dominates the assets of Indonesia’s financial services sector. This study employs a quantitative method with an associative causal approach. The data used are secondary data in the form of annual financial statements and closing stock prices of KBMI 3 and KBMI 4 banking companies during the 2020–2024 period. The sampling technique used was purposive sampling based on specific criteria, resulting in companies that met the research requirements. Data analysis was conducted using panel data regression with the assistance of EViews 13 software through classical assumption tests, panel data regression model selection, coefficient of determination testing, simultaneous testing (F-test), and partial testing (t-test). The results of this study indicate that simultaneously Return on Assets (ROA), Debt to Equity Ratio (DER), and Current Ratio (CR) have a significant effect on stock prices of KBMI 3 and KBMI 4 banking companies listed on the Indonesia Stock Exchange during the 2020–2024 period. Partially, Return on Assets (ROA) has a positive and significant effect on stock prices, while Debt to Equity Ratio (DER) and Current Ratio (CR) do not have a significant effect on stock prices. These findings indicate that investors place greater emphasis on company profitability compared to solvency and liquidity ratios when making investment decisions in the banking sector. This study is expected to provide theoretical contributions to the development of Agency Theory and fundamental analysis in the Indonesian capital market. Practically, the results of this study may serve as a consideration for investors in making investment decisions and for company management in improving financial performance to increase corporate value in the capital market.